The emergence of an adaptive response network: The April 20, 2013 Lushan, China Earthquake. (December 2016) - Zhang, Haibo; Zhang, Xiaosu; Comfort, Louise; Chen, Mengyao
Abstract: We employ a theoretical framework of complex adaptive networks to explore how China's comprehensive emergency management system, initiated after the SARS Epidemic, adapts to extreme disasters in the centralized political context of China. Based on the multi-organizational responses to the Ya'an Earthquake, April 20, 2013, China, we identify the emergence of the response network, and analyze the interactions among organizations and information infrastructure supporting such interactions. Our findings suggest that a network structure, with expansion in both size and variation, emerged after the Lushan Earthquake. Emergence of this response network is determined by not only interorganizational interactions among public organizations and public service entities, but also cross sector interactions between public organizations and private and nonprofit organizations. However, interactions are insufficient not only between public organizations and private and nonprofit organizations, but also among public organizations at the municipal and county levels, particularly in the initial stage of the response. The lack of cross sector interactions between public organizations and private and nonprofit organizations limits command and coordination of the whole network in achieving a collective performance. Accordingly, in information processes, communication infrastructure was not sufficiently strong to support these two types of interactions. Policy recommendations are offered to improve preparedness of the response plans, emergence of response networks, as well as information infrastructure to support interactions among organizations in disaster operations.